2015
DOI: 10.1039/c5cp00162e
|View full text |Cite
|
Sign up to set email alerts
|

The propargylbenzene dimer: C–H⋯π assisted π–π stacking

Abstract: The propargylbenzene dimer was investigated using mass selected electronic and infrared spectroscopy in combination with quantum chemical calculations. The IR spectrum in the acetylenic C-H stretching region indicates that the two propargylbenzene units in the dimer are in an almost identical environment. The stabilization energies calculated at various levels of theory predict that the anti-parallel structure is the most stable isomer. The observed spectra are assigned to π-stacked structures which incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
2
19
1
Order By: Relevance
“…Previous studies concerning the structure of ethylbenzene, styrene and phenylacetylene, are limited. Ab initio studies of the structure of phenylacetylene showed that the most stable (global minimum) is the anti‐parallel arrangement; however, other parallel orientations were also found to be highly probable . In the present experimental investigation, the most preferable orientation for the closest coordinating molecules were found to be in a parallel arrangement.…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…Previous studies concerning the structure of ethylbenzene, styrene and phenylacetylene, are limited. Ab initio studies of the structure of phenylacetylene showed that the most stable (global minimum) is the anti‐parallel arrangement; however, other parallel orientations were also found to be highly probable . In the present experimental investigation, the most preferable orientation for the closest coordinating molecules were found to be in a parallel arrangement.…”
Section: Resultscontrasting
confidence: 42%
“…Ab initio studies of the structure of phenylacetylenes howedt hat the most stable (globalm inimum) is the anti-parallel arrangement;h owever, other parallelo rientations were also found to be highly probable. [49][50][51] In the present experimental investigation, the most preferable orientation fort he closest coordinating molecules were found to be in ap arallel arrangement. The two structures for perpendicular molecules, in which two CÀH···p hydrogen bonds betweenp henylacetylene molecules are present, [49,50] were also found as al ocal minimum, but the stabilization energy is less favourable than for parallelo rientation.…”
Section: Resultsmentioning
confidence: 44%
“…S7B). The stabilizing influence of electrostatics in addition to dispersion energy in the π-stacked complexes has been observed in gas-phase studies (43,44). A parallel conformation of W289 in the DPH model results in a mean SAPT0 energy of -5.75 kcal .…”
Section: Tryptophan (W289) Dynamicsmentioning
confidence: 76%
“…As an illustrative example, the rotational spectrum of the benzene dimer contributed to the theoretical dispute between the observed T-shape and the alternative parallel geometry . Most of the gas-phase stacking experiments have used double-resonance IR-UV spectroscopy, but their vibrational signatures are usually of low resolution. Microwave spectroscopy provides accurate structural descriptions through the moments of inertia. , However, there are just a few rotational investigations of π-stacking clusters.…”
mentioning
confidence: 99%